2021
DOI: 10.5489/cuaj.7551
|View full text |Cite
|
Sign up to set email alerts
|

Compression or obstruction: Prospective analysis of the function of the adjustable transobturator male system (ATOMS) based on pre- and postoperative urodynamic data

Abstract: Introduction: This analysis, based on pre- and postoperative urodynamic data, is the first to elucidate the influence of the adjustable transobturator male system (ATOMS, A.M.I. GmbH, Feldkirch, Austria) on the lower urinary tract and disclose possible obstructive properties. Methods: A prospective study was performed in patients who had stress urinary incontinence and were scheduled for ATOMS implantation after radical prostatectomy. Apart from continence assessment (24-hour pad test, International Consultati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…e lack of considerable postoperative results in the selected studies in terms of pad weight does not consent to evaluate the effect of the different groups of devices on this parameter. More data are available in terms of number of pad/day, and in all groups, a significant (P < 0.01) mean reduction was observed after treatment, with the lowest improvement (−2.0 (95% CI −1.43/−2.57) pad/day) in the group of bulking agents and the highest (−5.19 (95% CI Van Uhm (39) Bauer (32) Bauer (31) Bauer (12) Ferro (29) Collado (15) Collado (14) Bauer (43) Renè Yiou (30) Cestari (40) Kim (34) Correira Lima (33) Renè Yiou ( Test of θ i = θ j : Q(0) = -0.00, p = .…”
Section: Advances In Urologymentioning
confidence: 87%
See 1 more Smart Citation
“…e lack of considerable postoperative results in the selected studies in terms of pad weight does not consent to evaluate the effect of the different groups of devices on this parameter. More data are available in terms of number of pad/day, and in all groups, a significant (P < 0.01) mean reduction was observed after treatment, with the lowest improvement (−2.0 (95% CI −1.43/−2.57) pad/day) in the group of bulking agents and the highest (−5.19 (95% CI Van Uhm (39) Bauer (32) Bauer (31) Bauer (12) Ferro (29) Collado (15) Collado (14) Bauer (43) Renè Yiou (30) Cestari (40) Kim (34) Correira Lima (33) Renè Yiou ( Test of θ i = θ j : Q(0) = -0.00, p = .…”
Section: Advances In Urologymentioning
confidence: 87%
“…All 36 studies [ 9 43 ] were prospective mono- or multicenter clinical trials, and only 1 was randomized [ 9 ] ( Table 1 ).…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Since 2009, the ATOM System has been used for the treatment of mild to moderate stress incontinence, but assumptions about its functioning have only been made in recent years. Virseda et al and Queissert et al have shown that the unilateral compression of the urethra does not result in obstructive micturition at normal adjusted volumes, and they concluded that the urethra can deflect in other directions due to the unilateral compression [ 8 , 9 ]. However, they did not provide any evidence for the assumption that indirect support of the membranous sphincter results from this.…”
Section: Discussionmentioning
confidence: 99%
“…We have recent urodynamic evidence that ATOMS placement does not cause obstruction itself during the voiding phase [ 19 , 20 ], but there is no specific study addressing the role of previous solved obstruction in patients receiving ATOMS. On the one hand, despite patients with stricture being at risk of disease recurrence that could impact the long-term functional results, we did not detect a case of stricture recurrence after a median follow-up of 51 months, provided stable urethral patency for at least 6 months was confirmed before ATOMS implant.…”
Section: Discussionmentioning
confidence: 99%